2018
DOI: 10.1021/acs.jpcc.8b08451
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Hydride Ions in Metal Hydride-Reduced BaTiO3 Samples Investigated with Quasielastic Neutron Scattering

Abstract: Perovskite-type oxyhydrides, BaTiO3–x H x , have been recently shown to exhibit hydride-ion (H–) conductivity at elevated temperatures, but the underlying mechanism of hydride-ion conduction and how it depends on temperature and oxygen vacancy concentration remains unclear. Here, we investigate, through the use of quasielastic neutron scattering techniques, the nature of the hydride-ion dynamics in three metal hydride-reduced BaTiO3 samples that are characterized by the simultaneous presence of hydride ions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 52 publications
4
21
0
1
Order By: Relevance
“…We found that in BaTiO 3 the required energy for this process is 2.4 eV, which, in agreement with previous results, 7,8 is considerably larger than the typical activation energy for hydride-ion conduction in this system (<0.5 eV). 4,8 Thus, we have no reason to expect that the indirect interstitial mechanism takes place in BaTiO 3 , which is in full accordance with the absence of any signature of O-H species in the vibrational spectra.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…We found that in BaTiO 3 the required energy for this process is 2.4 eV, which, in agreement with previous results, 7,8 is considerably larger than the typical activation energy for hydride-ion conduction in this system (<0.5 eV). 4,8 Thus, we have no reason to expect that the indirect interstitial mechanism takes place in BaTiO 3 , which is in full accordance with the absence of any signature of O-H species in the vibrational spectra.…”
Section: Discussionsupporting
confidence: 54%
“…The results of the average structural and thermal characterisation of CA1, CA2 and NAB were reported and discussed elsewhere. 4,13 The characterisation of CA3, together with that of CA2 and NAB, can be found in Fig. 1(a-c) shows the INS spectra of CA1, CA2, CA3, and NAB at T < 10 K, as measured on (a) MERLIN (CA2 and CA3), (b) TOSCA (CA1, CA2 and CA3), and (c) VISION (NAB), respectively.…”
Section: Average-structural and Thermogravimetric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The details of the sample preparation can be found in ref. 41 and the present work makes use of the sample denoted as CA1 in ref. 41.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Powder X-ray diffraction (PXRD) measurements conrmed a simple cubic structure for the sample with lattice parameter a ¼ 4.0055Å at ambient temperature. 41 Thermogravimetric analysis (TGA) of the sample showed that the total defect concentration x, as in BaTiO 3Àx H y , xÀy , was x ¼ 0.18, 41 where , denotes oxygen vacancies in the oxyhydride. The hydride ion concentration was determined to be y ¼ 0.10 using nuclear magnetic resonance (NMR) spectroscopy, 41 which implies an oxygen vacancy concentration of (x À y) ¼ 0.08.…”
Section: Sample Preparationmentioning
confidence: 99%